Psycho-demographic factors as determinants of perceived accident vulnerability among commercial motorcyclists in two Nigerian cities (2011)
This study investigated the influence of psychological and socio-demographic factors on perceived vulnerability to road accidents (VTRA) among commercial motorcyclists. The cross-sectional survey included 292 participants following multi-stage sampling. A 65-item questionnaire was used for data collection. Analysis included ANOVA, regression, t-test, and descriptive statistics. Results showed that aged commercial motorcyclists operating in Ibadan with poor knowledge of road signs, who also rarely use psychoactive substances (n=25, =18.0), as well as aged motorcyclists operating in Ibadan with poor knowledge of road signs, who rarely use substances (n=21, = 18. 0) reported the highest level of perception of VTRA. Substance use pattern (F (292) = 51.25, P < 0.01), personality (F (292) = 4. 70, P < 0.001), and a combination of substance use pattern, personality, location, and road signs knowledge (F (292) = 6.94, P <0.01) significantly influenced perceived accident vulnerability among participants. Experience in riding commercial motorcycles (t (292) = 1.299,df =289, p<.05), and location/city (n=292, t= 1.688, p<.05) also significantly predicted perception of VTRA (t (292) = 1.299, p<.05). This highlights the importance of substance use, personality factors (openness and agreeableness), and experience as factors critical to the understanding of 'perception of VTRA, suggesting the need for strengthening anti-drug campaign, as well as psychological/personality testing in reducing road traffic accidents involving commercial motorcyclists.